CACNA1H antibodies associated with headache with neurological deficits and cerebrospinal fluid lymphocytosis (HaNDL) - Kürtüncü, Murat; Kaya, Dilaver; Zuliani, Luigi; Erdağ, Ece; İçöz, Sema; Uğurel, Elif; Çavuş, Filiz; Ayşit, Neşe; Birışık, Ömer; Vincent, Angela; Eraksoy, Mefkure; Vural, Burçak; et al. (Sage Publications Ltd, 2013)
Background: Patients with the syndrome of headache with neurological deficits and lymphocytosis (HaNDL) typically present with recurrent and temporary attacks of neurological symptoms and cerebrospinal fluid lymphocytosis. Aim and methods: To identify potential HaNDL-associated antibodies directed against neuronal surface and/or synapse antigens, sera of four HaNDL patients and controls were screened with indirect immunohistochemistry, immunofluorescence, cell-based assay, radioimmunoassay, protein macroarray and enzyme-linked immunosorbent assay (ELISA). Results: Although HaNDL sera did not yield antibodies to any of the well-characterized neuronal surface or synapse antigens, protein macroarray and ELISA studies showed high-titer antibodies to a subunit of the T-type voltage-gated calcium channel (VGCC), CACNA1H, in sera of two HaNDL patients. Conclusion: Our results support the notion that ion channel autoimmunity might at least partially contribute to HaNDL pathogenesis and occurrence of neurological symptoms.
WOS: 000312550000006
PubMed ID: 23111027
Keywords: HaNDL; Headache; CACNA1H; Voltage-Gated Calcium Channel; Autoantibody